Analisis Kelayakan Finansial Agribisnis Ternak Kambing di Kota Kendari - Rosmawaty, Rosmawaty; Hafid, Harapin (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
The research objectives were to know financial feasibility Analysis of goats husbandry in Kendari city. This research was conducted in Kendari City, from March through April 2009 with samples determined Random Sampling each other 30 persons of a stockman. Data were collected from the director of the interview and analyzed with analysis of financial feasibility analysis. Results of this research were showed that: financial agribusiness of goats was proper to effort in Kendari city. It was based on an assessment of investment properly, where discount factor 15% got a value of NPV>0 there was Rp. 6.122.128, NBCR>1 there was 2,665 and value of IRR> BI rate was 70,42%.